2014
DOI: 10.1242/jcs.146894
|View full text |Cite|
|
Sign up to set email alerts
|

The endocytic activity of the flagellar pocket in Trypanosoma brucei is regulated by an adjacent phosphatidylinositol phosphate kinase

Abstract: Phosphoinositides are spatially restricted membrane signaling molecules. Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2), a phosphoinositide highly enriched in and present throughout the plasma membrane, has been implicated in endocytosis. Trypanosoma brucei has one of the highest known rates of endocytosis, a process it uses to evade the immune system. To determine whether phosphoinositides play a role in endocytosis in this organism we have identified and characterized one of the enzymes responsible for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 125 publications
3
47
0
Order By: Relevance
“…These results suggest that the primary site of PI(3,5)P 2 synthesis is on late endosomal, and to a lessor extent lysosomal, membranes, but that the end product resides mostly in the lysosome. This is similar to the situation with PI(4,5)P 2 , where the kinase (TbPIPKA) localizes anterior to the mouth region of the flagellar pocket, but the product localizes quite distinctly to the flagellar pocket proper [56]. …”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These results suggest that the primary site of PI(3,5)P 2 synthesis is on late endosomal, and to a lessor extent lysosomal, membranes, but that the end product resides mostly in the lysosome. This is similar to the situation with PI(4,5)P 2 , where the kinase (TbPIPKA) localizes anterior to the mouth region of the flagellar pocket, but the product localizes quite distinctly to the flagellar pocket proper [56]. …”
Section: Discussionsupporting
confidence: 65%
“…Uptake of endocytic cargo including tomato lectin and transferrin (not shown) was unaffected. This contrasts with depletion of two other PIP's, PI3P (TbVps34 knockdown) and PI(4,5)P 2 (TbPIPKA knockdown), both of which result in defective endocytosis [56, 57], and further supports the specific assignment of TbFab1 activity to PI(3,5)P 2 . In addition, lysosomal delivery, measured as decline in FITC fluorescence as cargo moved to more acidic compartments, was unimpaired by TbFab1 depletion.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…For instance, it has recently been shown that a phosphatidylinositol 4-phosphate 5-kinase, TbPIPKA, is present in the FPN (53). This kinase manufactures the phosphatidylinositol 4,5-bisphosphate that is essential for endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al showed that the 5-phosphatase function of INPP5E is counteracted by the PI4P 5-kinase PIPKIγ and that enrichment of PI(4,5)P 2 at the base of the cilium is critical for ciliogenesis [71**]. A PI(4,5)P 2 -enriched zone at the base of the cilium has also been found in T. brucei and C. elegans [53**,72]. Since PI(4,5)P 2 effector proteins include the exocyst, septins, tubby family proteins, and clathrin adaptor proteins [73-76], a PI(4,5)P 2 -enriched domain could mark the ciliary pocket as a specialized site for vesicle exocytosis and endocytosis (Figure 3).…”
Section: Generating a Unique Ciliary Lipid Contentmentioning
confidence: 99%